Problem-Solving Courts in Comparative Law: Combination of Therapy and Responsibility - Tešović, Olga (NBP. Nauka, bezbednosti, policija, 2024)
This paper examines the innovative approach of problem-solving courts within the framework of comparative law, emphasizing the integration of therapeutic jurisprudence and individual criminal responsibility. By analyzing various models from different jurisdictions, the study highlights how these courts effectively address underlying issues in criminal behavior, such as substance abuse and mental health problems, through tailored interventions. The research draws on a comparative analysis to explore the effectiveness of these courts in reducing recidivism, enhancing offender rehabilitation, and promoting social reintegration. The paper also discusses the challenges and potential of this approach in balancing the goals of therapy and legal accountability. Through a comprehensive review of judicial, and policy frameworks, this study provides valuable insights into the evolving role of the judiciary in addressing complex social issues and the potential of problem-solving courts as a transformative tool in the criminal justice system.
Keywords: Problem-solving courts – Therapeutic justice - Drug courts - Mental health in law - Offender rehabilitation - Judicial innovation